Improving Inventory Management in Indonesian Government: IT, HR Capacity, and the Role of Financial Reporting - Antonius,; Juliana, Ahmad; Putri, Anisa; AB, Nizhamuddin; Lada, Suddin (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study investigates how information technology and human resource capacity influence inventory management, moderated by financial statement quality. It contributes to the limited literature on the intersection of IT, HR, and financial transparency in enhancing public sector inventory performance in Indonesia. Using a quantitative approach, data were collected from 153 organizational units’ head within a local government in Malinau, Indonesia, analyzed through Partial Least Squares (PLS). Findings reveal that both information technology and HR capacity significantly improve inventory management. However, the moderating effect of financial statement quality weakens this relationship, suggesting a disconnect between reporting practices and operational integration. Theoretically, the study broadens understanding of how financial reporting quality interacts with organizational capabilities in public governance. These findings call for managers to not only invest in systems and personnel but also to align financial transparency mechanisms to ensure coherent and effective inventory control.